2014
DOI: 10.1371/journal.pone.0096725
|View full text |Cite
|
Sign up to set email alerts
|

c-kit+ Cardiac Stem Cells Alleviate Post-Myocardial Infarction Left Ventricular Dysfunction Despite Poor Engraftment and Negligible Retention in the Recipient Heart

Abstract: Although transplantation of c-kit+ cardiac stem cells (CSCs) has been shown to alleviate left ventricular (LV) dysfunction induced by myocardial infarction (MI), the number of exogenous CSCs remaining in the recipient heart following transplantation and their mechanism of action remain unclear. We have previously developed a highly sensitive and accurate method to quantify the absolute number of male murine CSCs in female recipient organs after transplantation. In the present study, we used this method to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 38 publications
13
199
0
1
Order By: Relevance
“…Clearly, given the lack of significant new myocyte formation (Figure 7C), CPCs exerted their salubrious actions via paracrine mechanisms, as previously reported 3, 8. Such paracrine actions may have been exerted not only by CPCs residing in the myocardium, but also by CPCs retained in other organs such as the lungs, since a large number of CPCs delivered intracoronally are found outside of the heart, primarily in the lungs 5, 6. Regardless of the exact source (cardiac versus extracardiac) of paracrine factors, our data indicate that the duration of myocardial exposure to paracrine factors may be more important than the intensity of the exposure.…”
Section: Discussionsupporting
confidence: 54%
“…Clearly, given the lack of significant new myocyte formation (Figure 7C), CPCs exerted their salubrious actions via paracrine mechanisms, as previously reported 3, 8. Such paracrine actions may have been exerted not only by CPCs residing in the myocardium, but also by CPCs retained in other organs such as the lungs, since a large number of CPCs delivered intracoronally are found outside of the heart, primarily in the lungs 5, 6. Regardless of the exact source (cardiac versus extracardiac) of paracrine factors, our data indicate that the duration of myocardial exposure to paracrine factors may be more important than the intensity of the exposure.…”
Section: Discussionsupporting
confidence: 54%
“…For instance, our group has previously shown that ~99% of transplanted CPCs were undetected in the heart at 35 days post implantation [21,22]. Thus, strategies that can enhance CPC survival after adoptive transfer are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the previous data that show the therapeutic potential of CPC for heart repair after MI, some studies have shown multiple shortcomings with the use of CPCs, including poor survival of the transplanted cells as well as lack of differentiation into mature cardiomyocytes [11,17,21,22] (See below for more details). Addressing these issues may enhance the beneficial effects of CPCs for heart repair.…”
Section: Cpc Therapy For Ischemic Cardiomyopathy Following MImentioning
confidence: 99%
See 1 more Smart Citation
“…The overall retention of cells observed at 24 h (~4-5%) was 51 comparable to that observed in previous preclinical and clinical investigations using a variety of cell types. 26,52,141,160,162,163,[165][166][167] Therefore, intracardiac retention may be more related to route of administration rather than cell type whether intrinsically native heart or from extra-cardiac organs. We found a relatively high level of radioactivity in the apical portions of the right ventricular wall (Fig.…”
Section: Csc Distribution In Noncardiac Tissuesmentioning
confidence: 99%